2014
DOI: 10.1159/000358141
|View full text |Cite
|
Sign up to set email alerts
|

Is Rifaximin Effective in Maintaining Remission in Crohn's Disease?

Abstract: Background: Recent studies indicate that persistent intestinal inflammation in patients with Crohn's disease (CD) might be caused by abnormal intestinal microbiota. This hypothesis may suggest a beneficial effect of antibiotics in CD therapy. So far, guidelines do not recommend antibiotics except in the treatment of complicated CD, and there are few studies on the effects of rifaximin in these patients. Methods: Between December 2011 and December 2012, we performed a blinded randomized trial in 168 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…This antibiotic has been found to have broad-spectrum activity against most enteric pathogens, including Gram-positive, Gram-negative, aerobic and anaerobic species [74]. Additionally, randomized-controlled trials have demonstrated superiority of rifaximin when compared with placebo in inducing remission in CD patients [75] as well as sustaining remission in those who have already achieved remission with standard prednisone treatment [76].…”
Section: Rifaximinmentioning
confidence: 99%
“…This antibiotic has been found to have broad-spectrum activity against most enteric pathogens, including Gram-positive, Gram-negative, aerobic and anaerobic species [74]. Additionally, randomized-controlled trials have demonstrated superiority of rifaximin when compared with placebo in inducing remission in CD patients [75] as well as sustaining remission in those who have already achieved remission with standard prednisone treatment [76].…”
Section: Rifaximinmentioning
confidence: 99%
“…However, studies could not show any benefit of adding antibiotics to maintenance therapy [95]. However, in a randomizedcontrolled trial, the remission rate was still higher in the rifaximin group compared with the placebo group at the end of 1 year of follow-up [106]. Further studies are needed to clarify the role of rifaximin in the maintenance of CD.…”
Section: Efficacy Of the Drugs Used For Maintenance Therapymentioning
confidence: 99%
“…In general, the 4 trials were small in size and determined that clofazimine was not associated with a therapeutic benefit. A 2014 trial by Jigaranu et al [34] found that a 12-week course of twice daily rifaximin (800 mg) in addition to standard therapy maintained remission (CDAI <150) for 12 weeks and coincided with a 100-point drop in baseline remission score. The potential benefit of the rifampin antibiotic class was not seen in the multi-antibiotic trial including 450 mg/day rifabutin by Selby et al [27] .…”
Section: Crohn's Disease: Induction Of Remission -Perianal Fistulamentioning
confidence: 99%
“…The potential benefit of the rifampin antibiotic class was not seen in the multi-antibiotic trial including 450 mg/day rifabutin by Selby et al [27] . Meanwhile, the single dose of rifampin in the 1994 trial by Prantera et al [ 49 ] was likely not responsible for the increased rates of maintained remission in the experimental cohort [34] . Interestingly, Jigaranu et al [34] found that a 12-week dosing regimen of rifaximin gave a durable benefit 36 weeks later.…”
Section: Crohn's Disease: Induction Of Remission -Perianal Fistulamentioning
confidence: 99%
See 1 more Smart Citation